2021
DOI: 10.1186/s12884-021-04157-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with severe anaemia post-caesarean section at a tertiary Hospital in Southwestern Uganda

Abstract: Background Severe anaemia after caesarean section adversely affects the woman and the new-born. While prenatal anaemia is extensively studied, the literature on post-caesarean section anaemia is limited and characteristics of women at the highest risk of developing severe anaemia after caesarean section are unknown. This study aimed to determine the prevalence and factors associated with severe anaemia on day three post caesarean section. Methods O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“… 28 However, other studies did not show this association. 8 , 29 Emergency CD carries the risk of intraoperative complications and haemorrhage with an increased need for blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 However, other studies did not show this association. 8 , 29 Emergency CD carries the risk of intraoperative complications and haemorrhage with an increased need for blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative anaemia as a risk factor for transfusion has been reported in many studies. 5 , 12 , 29 , 30 Women who had preoperative anaemia were less tolerant of any amount of blood loss during surgery. A recent meta-analysis showed that the pooled prevalence of anaemia among pregnant women in Sudan was 53%.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean surgery is an operation incurring a moderate risk of bleeding, and rates are rising globally (Ferguson & Dennis, 2018). Women with a low preoperative Hb concentration and fetuses with macrosomia may be targeted for screening and hemoglobin optimization before and during cesarean surgery (Sivahikyako et al, 2021). There are no practical guidelines for the identification and therapy of anemia and iron deficiency in the postoperative phase, although there are various guidelines for the management of anemia in surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of all surgical patients at Rivers State University Teaching Hospital Port-Harcourt, the prevalence of post-operative anaemia was found to be 70% [7]. In Uganda, a study of post-caesarean section patients gave a post-operative severe anaemia prevalence of 6.79% [8]. In a secondary analysis of a prospective observational CESARO-study using 800 adult patients undergoing elective surgeries from various operative disciplines across seven hospitals ranging from university hospitals, district general hospitals to specialist clinics of minimally access surgery in Germany, the prevalence of post-operative anaemia was 49.2% [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some modifiable risk factors associated with anaemia include ignorance, illiteracy and poverty, and these factors are more in the developing countries of the world [4,10]. Post-operative anaemia is associated with various complications which may include wound sepsis, poor wound healing, pneumonia, venous thrombosis, stroke, delirium, acute myocardiac infarction and cardiac failure [8,[11][12][13][14][15]. All these can lead to increased cost of treatment and length of hospital stay Materials & Methods: This was a prospective, cohort study of women who had surgery at the ESUTH either for obstetric or gynaecological indications.…”
Section: Introductionmentioning
confidence: 99%